Strategies of Driving Academic Works for Developing Innovative Thinking Skills by Project-based Learning of Students at Sam Roi Yot Witthayakhom School under the Prachuap Khiri Khan Secondary Educational Service Area Office - Tharachiraset, Jinnanat; Panich, Anchana (Interdisciplinary Academic and Research Journal, 2023)
Innovative thinking skills are important skills in the 21st century. To develop students to have innovative thinking skills, teachers must encourage them to show their potential in the learning process. Therefore, the researcher was interested in conducting this research. The objectives of this research were to (1) study strategy for driving academic works to develop innovative thinking skills by using the project-based method, and (2) study the results of developing innovative thinking skills by using project-based learning management. The mixed method was used in this research. The population used in the research consisted of 85 students from Petch Ratchaphruek Project and 14 teachers from Sam Roi Yot Witthayakhom School under the Prachuap Khiri Khan Secondary Educational Service Area Office. The research tools were: 1) project-based learning plans, 2) students’ innovative thinking skills test, 3) students’ innovative thinking skills assessment form assessed by teachers, 4) strategy handbook for driving academic works to develop innovative thinking skills by using the project-based method, and 5) assessment form for using strategy handbook for driving academic works to develop innovative thinking skills by using the project-based method. The index of item-objective congruence (IOC) was between 0.67-1.00. The data were analyzed by using mean, standard deviation, and percentage of progress. The research result revealed that: (1) The strategy for driving academic works to develop innovative thinking skills of students by using a project-based method was participatory administration. And (2) The results of developing innovative thinking skills by using project-based learning management revealed that students had higher innovative thinking skills after learning than before learning with an average score increase of 9.48 points and progress of 47.41%.